Multifunctional protective strategies for wooden cultural heritage: antimicrobial efficacy of polyacrylic resins, siloxane coupling agents, and silver nanoparticles - Dumbravă, Andreea Ștefania; Corbu, Viorica Maria; Marinaș, Ioana Cristina; Pericleanu, Radu; Marinescu, Liliana; Motelica, Ludmila; Trusca, Doina Roxana; Ianovici, Nicoleta; Șesan, Tatiana Eugenia; Gheorghe-Barbu, Irina; Ficai, Denisa; Oprea, Ovidiu Cristian; et al. (Frontiers in Microbiology, 2025)
IntroductionThis study evaluates two innovative protective treatments for wooden cultural heritage objects vulnerable to biodeterioration. The first involves polyacrylic resin solutions embedded with silver nanoparticles (AgNPs), while the second uses the siloxane-based coupling agent 3-mercaptopropyltrimethoxysilane (3-MPTMS) to enhance AgNP adhesion to wood surfaces.MethodsAntimicrobial, anti-biofilm, and anti-metabolic activities were assessed using both qualitative and quantitative assays against biodeteriogenic strains (Penicillium chrysogenum, Bacillus cereus, and Bacillus megaterium). Additional analyses included extracellular nitric oxide (NO) production, phytotoxicity testing on Allium cepa, and correlations with biochemical parameters.ResultsPolyacrylic resins incorporating AgNPs exhibited significant antimicrobial properties, with stronger effects against bacteria. Treatments combining AgNPs with MPTMS or acrylic resins demonstrated enhanced inhibitory effect on microbial viability, adhesion, and degradative enzymes secretion. Sub-inhibitory concentrations of resin solutions modulated the extracellular NO levels, correlated with metabolic stress responses. Notably, ecotoxicity testing confirmed minimal phytotoxic impact, supporting the safety of these materials for cultural heritage applications.ConclusionThe findings support the use of AgNP-enhanced polyacrylic resins and silanized coatings as effective, non-destructive conservation strategies for wooden heritage artifacts, offering durable protection against microbial deterioration while maintaining environmental safety.